The Effectiveness of Scrabble Games Towards Students’ English Vocabulary Mastery at Junior High School Number 2 Jambi City - Sari, Anggi Widia; Ismiyati, Yanti; Munawwaroh, Khidayatul (Universitas Batanghari Jambi, 2023)
The purpose of this study was to find out the effectiveness of the scrabble game on students’ vocabulary mastery Junior High School Number 2 Jambi City. This research was conducted at Junior High School Number 2 Jambi City. In this research, the researcher use scrabble game as a media to increase students’ vocabulary mastery. The research aims to determine whether or not the scrabble game is effective in improving students' vocabulary mastery and tolearn about the students' responses to the scrabble game. The experimental design was used in this study. The study's subjects were ninth-grade students at Jambi City Junior High School Number 2. As a sample, the researcher attended two classes with 30 students each. The first class served as an experimental class with a scrabble game, while the second served as a control class without a scrabble game.A pretest and a posttest were used to collect the data. The scores before treatment were determined by the pretest score, and the scores after treatment were determined by the posttest score. The results of the pretest and posttest scores were analyzed using the t-test formula to determine whether or not the scrabble game is effective. The t-test was used to analyze data in this study using the Statistical Package for the Social Sciences (SPSS) for Windows version 25 program. The findings of this study revealed that the T-test was greater than the T-table (7.224 > 2.045) and the sig (2 tailed) result was less than the level of significance (0.00 < 0.05), implying that H1 was accepted while H0 was rejected. According to the results of the students, there was a significant improvement from the pre-test to the post-test, which was analyzed using SPSS. According to the explanation above, it is possible to conclude that scrabble games improve students' English vocabulary at Junior High School Number 2 Jambi City.